Pengembangan Modul Berbasis Edutainment untuk Meningkatkan Kemampuan Berpikir Kronologis Siswa - Haliza Putri; Zafri Zafri; Ofianto Ofianto (RC-INSTITUT, 2019)
This research is motivated by the unavailability of learning resources that maximally emphasize aspects of historical thinking, one of which thinks chronologically. One of the learning resources that can improve students’ chronological thinking ability is module based edutainment. This study aims to determine the feasibility, practicality, and effectiveness of modules based edutainment improve students’ chronological thinking ability. The research and development model used is 4D. Product trials were conducted at SMAN 5 Padang class XI IPS 1 in September-October 2017. The instrument of data collection using the questionnaire of the Likert scale. The data analysis techniques used are Qualitative and quantitative. The results showed that the feasibility of the material experts stated module based edutainment is feasible to use with the average data of research of 4.42, and 3.92 with the appropriate category according to expert materials. Effective research products improve students’ chronological thinking ability with n-gain 0.67 and are categorized as being. Research products are also categorized as very practical by teachers and students with a mean score of 4.40 and 4.16.